1998
DOI: 10.1254/jjp.77.61
|View full text |Cite
|
Sign up to set email alerts
|

Vascular α1-Adrenoceptor Subtype Selectivity and α1-Blocker-Induced Orthostatic Hypotension

Abstract: Newly developed alpha1-adrenoceptor antagonists including naftopidil are free from the "prazosin-like" side effect of orthostatic hypotension and associated symptoms. We investigated the mechanism for the differential effects of naftopidil and prazosin on the development of postural hypotension, with special attention on their selectivity for the alpha1-adrenoceptor subtype. We observed that head-up tilt caused a similar extent of drop in mean arterial pressure in control, naftopidil (1 mg/kg)- or prazosin (10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
15
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 19 publications
4
15
0
Order By: Relevance
“…Furthermore, drugs that have a higher a 1A -AR subtype selectivity would unlikely induce orthostatic hypotension. Recently, Take et al (28) reported that naftopidil, which has a relatively higher affinity for the a 1D -AR subtype than for the a 1A -and a 1B -ARs, did not cause orthostatic hypotension compared with prazosin. In the results of Take et al, the drug, which has a 1B-AR-low affinity, does not cause orthostatic hypotension and may have good tolerability in clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, drugs that have a higher a 1A -AR subtype selectivity would unlikely induce orthostatic hypotension. Recently, Take et al (28) reported that naftopidil, which has a relatively higher affinity for the a 1D -AR subtype than for the a 1A -and a 1B -ARs, did not cause orthostatic hypotension compared with prazosin. In the results of Take et al, the drug, which has a 1B-AR-low affinity, does not cause orthostatic hypotension and may have good tolerability in clinical use.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, adverse events often limit effective pharmacotherapy (de Mey, 2000). Postural hypotension or other cardiovascular side effects may be related to the relative lack of ␣ 1 -adrenoceptor subtype selectivity of agents such as terazosin and doxazosin as shown by the lower incidence of these events with tamsulosin (Take et al, 1998), a compound with high potency for ␣ 1A -adrenoceptors, albeit modest subtype selectivity (Hancock, 1996). A number of compounds highly selective for the ␣ 1A -adrenoceptor have been identified in recent years (Testa et al, 1994;Forray et al, 1995;Wetzel et al, 1995;Ford et al, 1996) in search of a uroselective agent for lower urinary tract symptoms associated with BPH, but to date, none have passed clinical development hurdles to validate the proposition that ␣ 1A -adrenoceptor selectivity can enhance the efficacy or reduce the side effect incidence more successfully than currently available agents.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, mice deficient in the ␣ 1B -adrenoceptor show diminished blood pressure responses to phenylephrine injection compared with homozygous controls (Cavalli et al, 1997). These observations suggest that ␣ 1B -adrenoceptors are more important for blood pressure regulation, and that compounds having reduced activity at ␣ 1B -sites compared with other ␣ 1 -adrenoceptors would be expected to cause fewer cardiovascular side effects than classical ␣ 1 -antagonists (Take et al, 1998), supporting the concept that an ␣ 1A -selective compound would be useful in BPH (Hancock et al, 1998a). Tamsulosin causes fewer hypotensive side effects in clinical practice (de Mey, 1998) and in animal studies (Hancock et al, 1998a,b), despite only moderate differences (Յ20 fold) in affinity at ␣ 1A -compared with either ␣ 1B -or ␣ 1D -adrenoceptors (Hancock, 1996).…”
mentioning
confidence: 97%
“…α1B-adrenoreceptors have been demonstrated to mediate both blood vessel contraction and baroreceptor-induced inotropic effects [25,26,27]. Moreover, tamsulosin has a higher selectivity for the α1B-adrenoreceptors than silodosin, and thus, the decrease in blood pressure induced by tamsulosin may be mediated by its blocking α1B-adrenoreceptors action on the participating in blood vessel contraction and baroreceptor-induced inotropic effects.…”
Section: Discussionmentioning
confidence: 99%